Resection of the Lateral Ear Canal in a Sheep with Zepp Technique - Alves, Teresa Souza; Gonzaga, Mariana da Costa; Rehbein, Letiana da Silva; Ribeiro, Elissa; Câmara, Antônio Carlos Lopes; Borges, José Renato Junqueira; Campebell, Rita de Cassia (Acta Scientiae Veterinariae, 2024)
Background: Otitis in farm animals’ compromises health and well-being, leading to economic losses, risk of herd infection and poor performance. In sheep, otitis is usually of bacterial or parasitic origin. Surgical treatment is routinely used in small animal practice, and it is also reported in the horses. Nevertheless, corrective surgery is considered an adjuvant to conservative therapy. Herein, we report the successful outcome in a case of otitis in sheep treated surgically by the technique of resection of the lateral auditory canal (Zepp procedure). Case: A 4-year-old crossbred ewe weighing 43 kg was referred for hospital care. Anamnesis revealed the history of placing an identification earring approximately 90 days before in the affected ear, which was removed due to infection in the region. Physical evaluation was performed, revealing edema, fetid odor, purulent discharge, aural hematoma and pain when handling the right pinna. Neurological examination revealed moderate rotation of the head to the right side, but without signs of involvement of the vestibular system. Otological examination of the vertical auditory canal showed inflammation, wall fibrosis, complete obstruction and a purulent fistula in the inner part of the external ear, making it impossible to perform an otoscopic evaluation of the auditory canal. Conservative treatment by needle puncture was successful resolving the aural hematoma. Although otitis was refractory to 5-days of medical treatment (systemic antibiotics and topical wound cleaning). After this period, there was still otologic secretion and correct cleaning of the auditory canal was unfeasible due to the severe auditory canal narrowing. Therefore, surgical treatment by resection the lateral wall of the external auditory canal (Zepp technique) was performed. Both surgery and post-operatory period were uneventful, and there was complete healing with good aesthetic results. Hospital discharge occurred on the 18th day after surgery. The ewe was followed-up during 23-months after regress to the flock, and there was no otitis recurrence. Discussion: Probably, in the present case, the presence of contamination with inappropriate placement of the identification earring, promoted aural hematoma, infection and pruritus, favoring the stenosis of the external auditory canal and the chronicity of the otitis. Identification of sheep by earrings must comply with a series of recommendations, from the choice of the adequate earring to the follow-up after its placement. Clinical signs of external otitis in sheep may include head shaking, ear itching with attempts to scratch with the limbs, pain during ear handling, and excessive cerumen at the base of the ear canal, as observed on the sheep herein. Treatment of external otitis in sheep should start with a conservative approach through daily cleaning that may be combined with antibiotics and anti-inflammatory therapies. Surgical procedure is indicated in cases refractory to medical treatment, allowing adequate drainage and ventilation of the auditory canal. In the sheep herein, final outcome was considered good, considering the absence of surgical site infection, dehiscence and recurrence. Thus, we concluded that the technique of resection of the lateral auditory canal (Zepp procedure) was effective in the sheep of this report, and may be a good alternative for the treatment of chronic otitis in sheep. Keywords: ear disorders, otitis, small ruminant, stenosis. Título: Ressecção do canal auditivo lateral em um ovino com a técnica de Zepp Descritores: afecções das orelhas, estenose, otite, pequenos ruminantes.